Putting Their Eggs in India’s Basket: What Vertical Integration, Church’s Chicken, and Globalization Mean to Increasing Chicken Consumption in India - Scott E Basford (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
India has the second largest population in the world and a rapidly growing economy, yet it lags far behind the world average in chicken meat consumption. Nonetheless, rates are increasing briskly and are expected to double within five years. Understanding the factors that contribute to this rise can provide broader insight into political, economic and social developments in Indian society. This paper reviews current and projected levels of chicken consumption across India through an investigation of current literatures which assert that a cultural dietary aversion to red meat, rising incomes, increased urbanization, lower consumer cost, and, most importantly, vertically integrated production systems have contributed to Indian growth in the chicken industry. These indicators are then synthesized with a case study of the expansion of Atlanta-based Church's Chicken into India, with special emphasis placed on those measures most central in both the literature and the company's business plans. I argue the strength of chicken consumption and Church's Chicken's expansion into the country is part of a larger process of globalization–a manifestation of the exportation of foreign technological and economic constructs to Indian society–and represents a forthright proxy measure of the rate of globalization taking hold in India.
Keywords: Globalization; India; Chicken